MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING TECHNICAL DRAWING - Boburmirzo Bakhodir ogli Ko‘kiyev (International Scientific and Current Research Conferences, 2025)
The article discusses methods of activating students in technical drawing, as well as pedagogical technologies.